-3(-v+1)+v=

Simple and best practice solution for -3(-v+1)+v= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(-v+1)+v= equation:


Simplifying
-3(-1v + 1) + v = 0

Reorder the terms:
-3(1 + -1v) + v = 0
(1 * -3 + -1v * -3) + v = 0
(-3 + 3v) + v = 0

Combine like terms: 3v + v = 4v
-3 + 4v = 0

Solving
-3 + 4v = 0

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + 4v = 0 + 3

Combine like terms: -3 + 3 = 0
0 + 4v = 0 + 3
4v = 0 + 3

Combine like terms: 0 + 3 = 3
4v = 3

Divide each side by '4'.
v = 0.75

Simplifying
v = 0.75

See similar equations:

| 9x+20=34-5x | | 5(x+1)+4=2(x-3) | | 6x+8-5x=4 | | -3(x+4)=-15 | | 21x=18x+16 | | (x+4)+(x+2)+x=(x+4)+(x+2)+x-22 | | -3j-(-4)=12 | | -2=4/5(3)+b | | 10x=4x+66 | | 33+x=4 | | 5(2x+2)=6x-3 | | 5x+(-11)=34 | | 2(3x+6)=42 | | 6-3(4-x)=10-4(2x-5) | | x^2+12x+191=0 | | 2x+4y=160 | | -2(3w+u)-6(u+w)= | | 11x^2+6x+12=0 | | -9x^2+18x=11 | | -9-p/4=5 | | 12n^4+8n=0 | | 4=0.8x-6 | | 9x+2y=-4 | | x^2-10x=13 | | -3(1+6t)=14-t | | 9+-2p=25 | | -(-2v+6)+v= | | 0.5x-0.6=0.6(2x-1)-0.14 | | -11+n/6=0 | | n^2+2n+3=0 | | x+2x+15=180 | | y=-7+6x |

Equations solver categories